MODELING THE BEHAVIOR OF ENTERTAINMENT CONTENT CONSUMERS TAKING INTO ACCOUNT DIGITAL TECHNOLOGIES - Olga Zyma (Інтегровані комунікації)
This article is dedicated to the study of the peculiarities of entertainment content consumption by young people in Ukraine in the context of digital transformation and the development of new information and communication technologies. The relevance of the topic is determined by the growing role of social networks, streaming services, and user-generated content platforms, which are increasingly replacing traditional media distribution channels such as television and print publications. The research aims to model the behavior of young people as consumers of entertainment content, taking into account digital technologies to improve the psychological well-being of youth and enhance the quality of media products.